Effects of vancomycin‐induced gut microbiome alteration on the pharmacodynamics of metformin in healthy male subjects - Eunwoo Kim; Andrew Hyoungjin Kim; Yujin Lee; Sang Chun Ji; Joo‐Youn Cho; Kyung‐Sang Yu; Jae‐Yong Chung (Wiley, 2021)
Abstract Metformin is a major treatment for type 2 diabetes. This study was conducted to investigate the impact of gut microbiome dysbiosis on the pharmacokinetics and antihyperglycemic effects of metformin. Healthy adult males aged 19-45 years with no defecation abnormalities were recruited for this 4‐period clinical study: baseline; post‐metformin (i.e., multiple oral doses of 1000 mg metformin on days 1-4); post‐vancomycin (i.e., multiple oral doses of 500 mg vancomycin on days 11-17 inducing gut microbiome changes); and post‐metformin + vancomycin (i.e., multiple oral doses of 1000 mg metformin on days 16-19). In each period, serum glucose and insulin concentrations following an oral glucose tolerance test, fecal samples for gut microbiome composition, and safety data were obtained. Following metformin dosing, plasma and urine samples for pharmacokinetics were collected. Nine subjects completed the study. The pharmacokinetics of metformin remained unchanged, and the antihyperglycemic effect was significantly decreased after vancomycin administration (p value = 0.039), demonstrating the weak relationship between the pharmacokinetics and pharmacodynamics of metformin. Relative abundances of some genus were changed after vancomycin administration, and tended to correlate with the antihyperglycemic effects of metformin (p value = 0.062 for Erysipelatoclostridium; p value = 0.039 for Enterobacter; and p value = 0.086 for Faecalibacterium). Adverse events occurred in all subjects and were resolved without sequelae. In conclusion, a decrease in the antihyperglycemic effect of metformin was observed after concomitant administration with vancomycin, without changes in metformin pharmacokinetics. The antihyperglycemic effect was tended to correlate with the relative abundance of several genus, suggesting that the effect of metformin is partly attributable to the gut microbiome (ClinicalTrials.gov, NCT03809260).